2008
DOI: 10.1002/ajh.21162
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for pulmonary artery systolic hypertension among sickle cell disease patients in Nigeria

Abstract: Pulmonary artery systolic hypertension is common and associated with increased mortality among adult sickle cell disease (SCD) patients in the United States. Although the prevalence of SCD is highest in subSaharan Africa, the frequency of pulmonary artery systolic hypertension and the risk factors for the development of pulmonary hypertension have not been reported from Africa. We studied 208 hydroxyurea naïve Nigerian SCD patients at steady state and 94 healthy controls. Pulmonary artery systolic hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
5
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 23 publications
11
96
5
6
Order By: Relevance
“…This signature was found to be composed of both novel and established PH candidate genes as evidenced by literature mining and the PubMed search tool. For example, ADORA2B, a candidate gene known to modify the severity of SCD (20,21), was recently identified via metabolomic profiling of a transgenic SCD mouse model with excessive adenosine signaling through the ADORA2B leading to sickling and hemolysis (22), processes known to be independently correlated with the presence of PH in SCD (13,23). Furthermore, ADC, another signature gene, which decarboxylates L-arginine to agmatine, is an established PAH candidate gene (24) and is potentially involved in SCD-related PH (25).…”
Section: Discussionmentioning
confidence: 99%
“…This signature was found to be composed of both novel and established PH candidate genes as evidenced by literature mining and the PubMed search tool. For example, ADORA2B, a candidate gene known to modify the severity of SCD (20,21), was recently identified via metabolomic profiling of a transgenic SCD mouse model with excessive adenosine signaling through the ADORA2B leading to sickling and hemolysis (22), processes known to be independently correlated with the presence of PH in SCD (13,23). Furthermore, ADC, another signature gene, which decarboxylates L-arginine to agmatine, is an established PAH candidate gene (24) and is potentially involved in SCD-related PH (25).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found an association of high hemoglobin F with lower pulmonary hypertension risk, [11][12][13][14] but several others have detected no such association. 1,2,[15][16][17][18] We recently reported a prospective, multicenter study of 310 children and adolescents with sickle cell disease at steady state in which tricuspid regurgitation velocity of 2.6 m/s or higher occurred in 11% of participants and had independent associations with hemolysis and hemoglobin oxygen desaturation. 3 In addition, we have found that an elevated screening tricuspid regurgitation velocity in children and adolescents with sickle cell disease predicts functional impairment over 2 years of follow-up (V.R.G., unpublished observations, April 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most common monogenetic disorders in the world, affecting nearly 1 in 600 African Americans (3) and an estimated 1 to 4% of babies born in sub-Saharan Africa (4). The resulting hemolytic anemia is most severe in patients homozygous for the sickle hemoglobin (HbS) gene mutation (Hb-b; glu6val).…”
mentioning
confidence: 99%